Manajemen Cairan pada Operasi Jantung - Kusuma Dewi, Ni Luh; Adi Parmana, I Made (Perdatin Pusat, 2014)
Terapi cairan merupakan salah satu topik paling kontroversial dalam manajemen perioperatif. Perdebatan yang terus berlangsung terutama mengenai jumlah dan tipe cairan resusitasi, metode monitoring dan strategi pemberian cairan pada operasi jantung. Laporan mengenai hipervolemia atau hipovolemia perioperatif semakin banyak dijumpai. Manajemen cairan perioperatif yang tidak tepat akan meningkatkan morbiditas dan mortalitas pasca pembedahan. Dalam tinjauan pustaka ini dipaparkan fisiologi cairan tubuh, respon tubuh terhadap stress pembedahan, patofisiologi kelebihan dan kekurangan cairan perioperatif pada operasi jantung, penggunaan alat monitoring, pemilihan jenis cairan serta dampak pada fungsi organ dan aplikasi klinis. Kata kunci: Cairan, koloid, kristaloid, operasi jantung Fluid Management in Cardiac Surgery Fluid therapy is one of the most controversial topics in perioperative management. There is continuing debate with regard to the quantity and the type of fluid resuscitation, the choice of parameters used in monitoring and goal directed therapy strategy used cardiac surgery. However, there are increasing reports of perioperative excessive and deficit intravascular volume leading to increased postoperative morbidity and mortality. This article aims to briefly review physiology of body fluid, stress response to surgery, pathophysiology of fluid excess and deficit during perioperative period in cardiac surgery, the use of monitoring, the fluid formula available, the effects to organ and clinical implications. Key words: Cardiac surgery, colloids, crystalloids, fluids Reference Perel P, Roberts I. Colloids versus crystalloids for fluid resuscitation in critically ill patients. Cochrane Database Syst Rev. 2012;6:CD000567. Shaw A, Raghunathan K. Fluid management in cardiac surgery. Anest Clin. 2013;31:269–80. Hahn RG. Volume kinetics for infusion fluids. Anesthesiology. 2010;113(12):470–81. Rhee P. Shock, electrolytes and fluids. Dalam: Towsend CM, Penyunting. Sabiston textbook of surgery: the biological basis of modern surgical practice. Edisi ke-17. Elsevier Saunders: Philadelphia; 2012,66–119. Chappell D, Jacob M, Hofmann-Kiefer K, dkk. A rational approach to perioperative fluid management. Anesthesiology. 2008;109(4):723–40. Finfer S, Bellomo R, Boyce N, dkk. A comparison of albumin and saline for fluid resuscitation in the intensive care unit. N Eng J Med. 2004;350(22):2247–56. Myburgh JA, Finfer S, Bellomo R, dkk. Hydroxyethyl starch or saline for fluid resuscitation in intensive care. N Eng J Med. 2012;367(20):1901–11. Perner A, Haase N, Guttormsen AB, dkk. Hydroxyethyl starch 130/0.42 versus Ringer’s acetate in severe sepsis. N Eng J Med. 2012;367(2):124–34. Woodcock TE, Woodcock TM. Revised starling equation and the glycocalyx model of transvascular fluid exchange: an improved paradigm for prescribing intravenous fluid therapy. Br J Anaesth. 2012;108(3):384–94. Kozar RA, Peng Z, Zhang R, dkk. Plasma restoration of endothelial glycocalyx in a rodent model of hemorrhagic shock. Anesth Analg. 2011;112(6):1289–95. Bruegger D, Rehm M, Abicht J, dkk. Shedding of the endothelial glycocalyx during cardiac surgery: on pump versus off pump coronary artery bypass graft surgery. J Thorac Cardiovasc Surg. 2009;138(6):1445–7. Chowdhury A, Cox E, Francis S, dkk. A randomized controlled, double blind crossover study on the effect of 2-L infusions of 0.9% saline and plasma-lyte(R) 148 on renal blood flow velocity and renal cortical tissue perfusion in healthy volunteers. Ann Surg. 2012;256(1):18–24. Kellum J, Song M, Almasri E. Hyperchloremic acidosis increases circulating inflammatory molecules in experimental sepsis. Chest. 2006;130(4):962–7. Albahrani M, Swaminathan M, Phillips-Bute B, dkk. Postcardiac surgery complications: association of acute renal dysfunction and atrial fibrillation. Anesth Analg. 2003;96(3):637–43. Neligan P. Monitoring and managing perioperative electrolyte abnormalities, acid base disorders and fluid replacement. Dalam: Longnecker DE, Penyunting. Anesthesiology. Edisi ke -2. New York: McGraw Hill, Inc; 2012,507–45. Jarvela K, Koskinen M, Kaukinen S, dkk. Effect of hypertonic saline (7.5%) on extracellular fluid volumes compared with normal saline (0.9%) and 6% hydroxyethyl starch after aortocoronary bypass graft surgery. J Cardiothorac Vasc Anesth. 2001;15:210–5. Verheij J, van Lingen A, Beishuizen A, dkk. Cardiac response in greater for colloid than saline fluid loading after cardiac or vascular surgery. Intensive Care Med. 2006;32:1030–8. Schortgen F, Lacherade JC, Bruneel F, dkk. Effect of hydroxyethylstarch and gelatin on renal function in severe sepsis: a multicentre randomized study. Lancet. 2001;357:911–6. Brunkhorst FM, Engel C, Bloos F, dkk. Intensive insulin therapy and pentastarch resuscitation in severe sepsis. N Engl J Med. 2008;358:125–39. Marik PE. Hemodynamic parameters to guide fluid therapy. Tansfusion Alt Transfusion Med. 2010;11(3):102–12. Habicher M, Perrino A, Spies C, dkk. Contemporary Fluid Management in Cardiac Anesthesia. J Cardiothorac Vasc Anesth. 2011;25(6):1141–53. Bennett-Guerrero E, Khan RA, Moskowitz DM, dkk. Comparison of arterial systolic pressure variation with other clinical parameters to predict the response to fluid challenges during cardiac surgery. Mt Sinai J Med. 2002;69:96–100. Wiesenack C, Prasser C, Keyl C, dkk. Assessment of intrathoracic blood volume as an indicator of cardiac preload: single transpulmonary thermodilution technique versus assessment of pressure preload parameters derived from a pulmonary artery catheter. J Cardiothorac Vasc Anaesth. 2001;15:584–8. Brock H, Gabriel C, Bibl D, dkk. Monitoringintravascular volumes for postoperative volume therapy. Eur J Anaesthesiol. 2001;19:288–94. Tousignant CP, Walsh F, Mazer CD. The use of transesophageal echocardiography for preload assessment in critically ill patients. Anesth Analg.2000;90:351–5. De Backer, dkk. In: Hemodynamic monitoring using echocardiography in the critically ill. Penyunting Springer-Verlag. Berlin Heidelberg; 2011:250–8.